Boundary element analysis of the stress intensity factors of plane interface cracks between dissimilarly adjoined anisotropic materials. (September 2019) - Shiah, Y.C.; Hwu, Chyanbin; Yao, Jin Jia
Abstract: For assuring structural integrity, the study of interface cracks has remained to be an important topic in engineering analysis. It is well known to have stresses with oscillatory singularity in the vicinity of crack tips between dissimilarly adjoined anisotropic materials. The present works targets plane analysis of the stress intensity factors (SIF) of interface cracks by the boundary element method (BEM). For modeling multiply adjoined domains, the conventional sub-region technique in the BEM is applied. For calculating the SIF of interface cracks, the path-independent H -integral is evaluated by the solutions of stresses and displacements at internal points along the integration path in each irrespective domain. For resolving the problem of near singularity when the internal Gauss points are close to the interfaces or crack surfaces, all boundary integrals are regularized to calculate the displacements and stresses at the internal points. From a few examples tested, the approach is verified to be very efficient for accurate assessment of the SIFs of interface cracks between dissimilarly adjoined anisotropic materials.